Production, characterization and properties of polysaccharide depolymerizing enzymes from a strain of Curvularia inaequalis - Gomes, E; Iembo, T; Da Silva, R (Folia microbiologica, 2001)
Xylanase, beta-glucosidase, beta-xylosidase, endoglucanase and polygalacturonase production from Curvularia inaequalis was carried out by means of solid-state and submerged fermentation using different carbon sources. beta-Glucosidase, beta-xylosidase, polygalacturonase and xylanase produced by the microorganisms were characterized. beta-Glucosidase presented optimum activity at pH 5.5 whereas xylanase, polygalacturonase and beta-xylosidase activities were optimal at pH 5.0. Maximal activity of beta-glucosidase was determined at 60 degrees C, beta-xylosidase at 70 degrees C, and polygalacturonase and xylanase at 55 degrees C. These enzymes were stable at acidic to neutral pH and at 40-45 degrees C. The crude enzyme solution was studied for the hydrolysis of agricultural residues.
Keywords: glykosidhydrolasy; zemědělské plodiny; Ascomycota; Crops, Agricultural; Culture Media; Fermentation; polysacharidy; Hydrolysis; Hydrogen-Ion Concentration; Polysaccharides; hydrolýza; Temperature; Glycoside Hydrolases; fermentace; teplota; koncentrace vodíkových iontů; kultivační média